Use of Pistacia terebinthus resin as immobilization support for Lactobacillus casei cells and application in selected dairy products - Schoina, Vasiliki (J Food Sci Technol, 2014)
Resin from Pistacia terebinthus tree was used for the immobilization of L. casei ATCC 393 cells. The encapsulated L. casei cells biocatalysts were added as adjuncts during yogurt production at 45 °C and probiotic viability was assessed during storage at 4 °C. For comparison reasons yogurt with free L. casei cells were prepared. The effect of encapsulated bacteria as adjuncts in yogurt on pH, lactic acid, lactose and other physicochemical parameters were studied for 60 storage days at 4 °C. Samples were also tested for the microbiological and organoleptic characteristics during storage at 4 °C. Encapsulation matrix seems to sustain the viability of embedded L. casei cells at levels more than 7 logcfug(−1) after 60 days of storage at 4 °C. Furthermore, the absence of pathogens such as Salmonella, Staphylococci, Enterobacteriaceae and coliforms in the produced yogurts is noteworthy where spoilage microorganisms such as yeasts and molds seem to affect yogurt quality only in absence of Pistacia terebinthus resin. The effect of the resin on production of aroma-related compounds responsible for yogurt flavor was also studied using the solid phase microextraction gas chromatography/mass spectrometry technique. Alpha and beta- pinene were the major aroma compounds detected in produced yogurts (over 60 % of total aromatic compounds detected). Yogurts with immobilized cells on P.terebintus resin had a fine aroma and taste characteristic of the resin.